Perilaku gizi dan faktor psikososial remaja obes - Noer, Etika Ratna; Kustanti, Erin Ratna; Fitriyanti, Addina Rizky (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background: Adolescent obesity is a complex condition involving medical, psychology and cultural issue. Changing dietary practices and an increasingly sedentary lifestyle predispose to obesity related nutritional behavior. Obese adolescents have impact on psychological problem, including stress, social discrimination, reduced self-esteem, self-dissatisfaction and resulting in lower quality of life.Objectives: This study describes nutritional behavior and psychosocial factors in overweight and obese adolescent. Methods: A qualitative study was conducted in the Public Senior High School (SMA 2) on July to August 2015, in Semarang City. In-depth-interview and Focus Group Discussion (FGD) were carried out with 20 of obese adolescent aged 15 to 17 years, 2 parents, 2 teacher and 2 friends. Thematic analysis is used to identify themes in a data.Results: The majority participants considered the timing of obese are when they reach puberty. The pattern of food habits of obese adolescents become unhealthy. Obese adolescents also feel the bullying or ridicule from friends, so that they psychologically disturbing. Environmental factors play a role in the incidence of obese adolescents, namely lack of control by parents. The parents say that obese adolescents are still in a reasonable level because the adolescent has not shown any serious health problems, but a sense of fear still owned by the parents of obese adolescents.Conclusion: The findings show obesity in adolescent has not been considered as health problem. Unhealthy diet, bullying, poor motivation and lack of peer supports are contributing factors in obese adolescent.Â